Rice husk biochar and inorganic fertilizer amendment combination improved the yield of upland rice in typical soils of Southern Guinea Savannah of Nigeria - Theophilus Isimikalu; John Olaniyan; Kehinde Affinnih; Okatahi Muhammed; Alexander Chubiojo Adede; Abdullahi Jibril; Emmanuel Atteh; Segun Yusuf; Taiye Juliana Ezekiel (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Rice is a staple food in Nigeria, but its cultivation faces constraints of soil acidity, low soil fertility and rainfall variability. Research has shown that biochar has the potential to alleviate the effects of these conditions, but responses vary depending on soil and climate factors. Therefore, this study was conducted to evaluate the effects of different application rates of rice husk biochar on upland rice growth and yield.Method Two field experiments were conducted within two years in Kwara State located in the southern Guinea savanna agroecological zone of Nigeria. Four biochar rates (0, 5, 15 and 25 t/ha) were used and replicated thrice in a randomised complete block design set up on three soils in three locations. Agronomic data were subjected to analysis of variance (ANOVA) to quantify variations in treatment responses, followed by a separation of significantly different means using the least significant difference (LSD) at p≤ 0.05.Results Better growth was recorded in the first year compared to the second year. Percentage decreases of 9.4 and 11.4% were recorded in plant height (12 weeks after planting), and tiller productivity from the first to the second year, respectively. Biochar amendment significantly (p≤0.01) improved rice seedling emergence (34.6%) and seed weight (5.8%) relative to control. The highest grain yield of 5.24 t/ha was recorded under 15 t/ha biochar application rate compared to 2.37 t/ha under control.Conclusion The application rate of 15 t/ha increased rice yield by 55.0% relative to the control, whereas at 25 t/ha the growth and yield were reduced.